2007
DOI: 10.3354/meps06917
|View full text |Cite
|
Sign up to set email alerts
|

Nanism (dwarfism) in fish: a comparison between red mullet Mullus barbatus from the southeastern and the central Mediterranean

Abstract: The gradient of environmental conditions from west to east in the Mediterranean results in very low primary productivity in the eastern area of this sea. This impoverishment is expressed also in higher trophic levels and has been accounted for by several faunistic phenomena. One of these is 'Levantine nanism' (dwarfism); this is characterized by smaller body size of specimens in the Levantine basin compared with conspecifics in the western Mediterranean. Nanism has been hypothesized for various taxonomic group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 26 publications
3
41
0
Order By: Relevance
“…The reason for this phenomenon is the unidirectional impact of 3 main environmental factors that are different between the eastern and western Mediterranean: productivity, temperature, and salinity (Sonin et al, 2007). This study, combined with previous results (Salman, 1998;Önsoy and Salman, 2005;Salman and Önsoy, 2010;Salman, 2011), testifies that Mediterranean nanism can also be seen in cephalopods.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…The reason for this phenomenon is the unidirectional impact of 3 main environmental factors that are different between the eastern and western Mediterranean: productivity, temperature, and salinity (Sonin et al, 2007). This study, combined with previous results (Salman, 1998;Önsoy and Salman, 2005;Salman and Önsoy, 2010;Salman, 2011), testifies that Mediterranean nanism can also be seen in cephalopods.…”
Section: Discussionsupporting
confidence: 58%
“…A phenomenon of so-called Mediterranean nanism had been suggested for various taxonomic groups of fishes and invertebrates such as sponges, crustaceans, and polychaetes (Sonin et al, 2007). The reason for this phenomenon is the unidirectional impact of 3 main environmental factors that are different between the eastern and western Mediterranean: productivity, temperature, and salinity (Sonin et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3). Despite the poor Levantine fishery suppositions made in various studies (Por, 1989, Sonin et al, 2007, these values are comparable to catch and discard rates reported for the central Mediterranean (Machias et al, 2001, D'Onghia et al, 2003, Sánchez et al, 2007. Discarded biomass alone, however, cannot represent the full extent of the impact of trawling on future year classes.…”
Section: Discards and Catch Compositionsupporting
confidence: 55%
“…This phenomenon was hypothesized by Por (1989) and demonstrated by Sonin et al, 2007 for the red mullet Mullus barbatus. The Levant is also consistently invaded by Indo-Pacific species (e.g.…”
Section: Introductionmentioning
confidence: 99%